A method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding

The preparation of gradient near-equiaxed Cr coatings through high-power pulse magnetron sputtering technology solves the problem of insufficient toughness of traditional Cr coatings, significantly improves the high-temperature oxidation resistance and toughness of zirconium alloy shells, and ensures that under harsh conditions corrosion resistance.

CN118460964BActive Publication Date: 2024-12-13SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410723483.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2024-12-13
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

The Cr coating prepared by traditional physical vapor deposition technology has a columnar crystal structure and is poor in toughness. It is prone to brittle cracking in high-temperature vapor environments, resulting in attenuation or loss of coating protective performance, and cannot effectively improve the high-temperature oxidation resistance of zirconium alloy shells. .

Method used

Using high-power pulse magnetron sputtering technology, the gradient near-equiax crystal Cr coating is prepared by regulating parameters such as bias voltage, target base distance, sputtering gas pressure and argon flow rate to form a three-layer structure and the first coating grains The size is 0.1-0.3 μm, the second coating is 1-2 μm, the third coating is 0.1-0.3 μm, and the total thickness is 10-15 μm, which enhances the toughness and thermal conductivity of the coating.

Benefits of technology

It significantly improves the high-temperature oxidation and toughness of the zirconium alloy shell, extends the service life, avoids the debonding and peeling of the coating under high temperature conditions, and ensures the corrosion resistance under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118460964B_ABST
    Figure CN118460964B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a gradient near-equiaxed crystal Cr coating on the surface of a zirconium alloy cladding, and belongs to the technical field of surface coatings for nuclear fuel claddings. The present invention adopts high-power pulsed magnetron sputtering technology, and independently transforms the HiPIMS equipment. Argon gas is introduced into the zirconium alloy cladding tube and the argon gas flow rate in the tube is controlled to regulate the tube wall temperature. The bias voltage, target-substrate distance, sputtering gas pressure and other parameters are comprehensively controlled to obtain a pure Cr near-equiaxed crystal coating on the surface of the zirconium alloy with three layers of gradient structure grains. The pure Cr coating on the surface of the accident-resistant zirconium alloy cladding designed by the present invention has good toughness, is not easy to fall off and crack, and a dense Cr2O3 protective oxide film can be generated on the surface when oxidized in a high-temperature steam environment, which significantly inhibits the diffusion of oxygen and improves the high-temperature oxidation resistance of the zirconium alloy cladding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nuclear fuel cladding surface coatings, and in particular relates to a method for preparing a gradient near-equiaxed crystal Cr coating on the surface of a zirconium alloy cladding. Background Art

[0002] Thanks to its good oxidation resistance, neutron irradiation resistance, high hardness, excellent ductility and extremely low thermal neutron absorption cross section, zirconium alloy has been used as a cladding material for UO2 fuel as early as 1950 and is still used today. However, in the case of a loss of coolant accident, once cooling water cannot be supplied in time, the core temperature will rise sharply, and zirconium alloy and water vapor will undergo oxidation reaction in a high temperature environment, producing hydrogen and releasing a large amount of heat, which can easily lead to catastrophic consequences such as hydrogen explosion and large-scale leakage of radioactive materials. Therefore, it is necessary to improve the ability of zirconium alloy cladding to resist high-temperature steam oxidation.

[0003] The development of coating materials is one of the key means to improve the high-temperature oxidation resistance of zirconium alloy cladding, and it is also one of the means with the greatest potential for engineering application. Among the many coating materials, pure Cr coating is the most widely studied candidate material with great application potential. As a coating material for accident-resistant fuel cladding, Cr has significant advantages such as high melting point, high thermal conductivity, strong resistance to high-temperature oxidation, and similar thermal expansion coefficient to zirconium alloy. However, the Cr coating prepared by traditional physical vapor deposition technology usually has a columnar crystal structure with poor toughness. When oxidized in a high-temperature steam environment, it is easy to cause brittle cracking along the vertical grain boundaries of the columnar crystals, resulting in the attenuation or even loss of the protective performance of the coating. Therefore, it is urgent to provide a preparation method for Cr coating suitable for zirconium alloy to improve its toughness, thereby effectively improving the ability of zirconium alloy fuel cladding to resist severe accidents. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the present invention proposes a method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding, wherein the coating has near-equiaxed crystal characteristics and is divided into three layers with a total thickness of 10-15 μm, wherein the first coating (the coating in contact with the substrate is the "first coating", and the coatings toward the air side are the "second coating" and "third coating" in sequence) has a grain size of 0.1-0.3 μm and a thickness of 5.0-7.0 μm; the second coating has a grain size of 1-2 μm and a thickness of 4.5-6.8 μm; the third coating has a grain size of 0.1-0.3 μm and a thickness of 0.5-1.2 μm.

[0007] The present invention also provides a method for preparing the above-mentioned gradient near-equiaxed crystal Cr coating on the surface of the zirconium alloy cladding, comprising the following steps:

[0008] The pretreated zirconium alloy substrate is subjected to target pre-sputtering treatment and argon plasma etching treatment, and then a Cr coating is sputtered to obtain the gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding;

[0009] Among them, in the process of sputtering Cr coating, three-layer coatings with different grain sizes and gradient near-equiaxed crystal structure characteristics are obtained through the following strategies. In practical applications, the adjustment of one parameter will affect the change of all parameters. Therefore, it is not possible to obtain the target product by changing a single variable, but an overall coordinated adjustment is required:

[0010] A. Regulating the bias voltage: When preparing the first coating or the third coating, the bias voltage is regulated to -110 to -120 V (including -110 V); when preparing the second coating, the bias voltage is regulated to -90 V to -110 V (excluding -110 V);

[0011] B. Adjust the target-substrate distance: when preparing the first coating or the third coating, the target-substrate distance is 15-20 cm; when preparing the second coating, the target-substrate distance is 10-15 cm.

[0012] C. Regulating the sputtering pressure: When preparing the first coating or the third coating, the sputtering pressure is 0.2-0.6Pa; when preparing the second coating, the sputtering pressure is 0.6-1.0Pa;

[0013] D. Regulating the argon flow rate and tube wall temperature in the tube: When preparing the first coating or the third coating, the argon flow rate in the tube is controlled to 25-50 sccm to adjust the tube wall temperature to 150-260°C; when preparing the second coating, the argon flow rate in the tube is controlled to 10-25 sccm to adjust the tube wall temperature to 260-420°C.

[0014] Furthermore, the total deposition time of the three coatings is 5-15 hours. When sputtering the first coating, the deposition time is 2.5-8 hours; when sputtering the second coating, the deposition time is 2-6 hours; when sputtering the third coating, the deposition time is 0.5-1 hour.

[0015] Furthermore, the pretreatment method is: using 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper to grind the surface of the zirconium alloy substrate in sequence, and then polishing it with 9μm, 3μm and 1μm diamond suspension in sequence; finally, immersing the sample in acetone solution for ultrasonic cleaning for 10-20 minutes, taking it out, drying it, and putting it in a vacuum box for standby use.

[0016] Furthermore, the parameters of the target pre-sputtering treatment are: the temperature of the magnetron sputtering chamber is 200-350°C, the chamber vacuum is 3-5×10 -4 Pa, high-purity argon gas is introduced to make the chamber pressure 0.8-1.5Pa, the power is 200-500W, and the sputtering time is 10-25min.

[0017] Furthermore, during the argon plasma etching process: temperature 200-350° C., argon gas flow rate 40-60 sccm, ion source current 0.5-2A, bias voltage -50 to -200V, etching time 10-30min.

[0018] Furthermore, in the process of sputtering the Cr coating: the pulse frequency is 200-500 Hz, the pulse width is 20-80 μs, the duty cycle is 1-4%, the sputtering power is 2000-4000 W, the deposition temperature is 150-420° C., and the deposition time is 5-15 h.

[0019] In the coating preparation process of the present invention, a high-power pulsed magnetron sputtering self-modification device (such as Figure 1 ), the device precisely controls the grain morphology and size of the plated pure Cr coating by adding an Ar flow rate control system in the zirconium alloy tube and a target-substrate distance dynamic adjustment system.

[0020] The application of the gradient near-equiaxed crystal Cr coating on the surface of the zirconium alloy cladding is to improve the high-temperature service performance of the zirconium alloy cladding tube.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] The present invention relates to a novel accident-resistant zirconium alloy cladding surface coating, the main component of which is pure chromium and presents a gradient near-equiaxed crystal structure. Since pure chromium has excellent corrosion resistance, the near-equiaxed crystal coating coated on the surface of the zirconium alloy cladding can significantly improve the material's resistance to high-temperature steam corrosion, help improve the zirconium alloy cladding's tolerance under harsh conditions, reduce the corrosion rate, and extend its service life. The unique structure of the pure Cr near-equiaxed crystal coating enables it to have good toughness (columnar crystal elongation 0.4%, near-equiaxed crystal elongation up to 3.0%), excellent stability, good thermal conductivity, and more uniform distribution of mechanical properties in high temperature environments (after testing, the gradient near-equiaxed crystal structure pure Cr coated zirconium alloy was subjected to high-temperature oxidation at 1200℃ water vapor for 3600s, and the oxide film and residual Cr coating did not peel off after oxidation. There was no debonding phenomenon at the coating-substrate interface, and no Cr coating peeling phenomenon caused by thermal stress. The film-substrate bonding force was good, and the Cr coating still had protective properties for the zirconium alloy substrate). This helps to improve the service life and performance of the zirconium alloy cladding under high temperature conditions and enhance the accident resistance of the zirconium alloy cladding.

[0023] The present invention adopts high-power pulsed magnetron sputtering technology and transforms the HiPIMS equipment to deposit a chromium coating with a thickness of 10-15μm on the surface of the Zr-4 alloy. The thermal environment during the sputtering process is dynamic. When there is a sufficient temperature gradient in the coating preparation process to provide sufficient thermal supercooling and promote atomic diffusion through a high nucleation rate, the formation of nearly equiaxed grains is induced. The present invention controls the deposition rate and cooling rate of the Cr coating by dynamically regulating parameters such as the argon flow rate in the sample tube during the sputtering process (i.e., regulating the tube wall temperature), bias voltage, target-substrate distance, and sputtering gas pressure, thereby obtaining a gradient nearly equiaxed Cr coating with grain sizes of 0.1-0.3μm, 1-2μm, and 0.1-0.3μm, respectively. The coating has smaller grains near the zirconium alloy substrate (grain size 0.1-0.3μm), and as the distance from the zirconium alloy increases, the grain size increases (grain size 1-2μm). The surface of the coating is composed of a layer of fine and dense fine crystals (grain size 0.1-0.3μm). This gradient near-equiaxed crystal structure can significantly improve the toughness of the zirconium alloy coating, prevent it from debonding and peeling during high-temperature oxidation, and ensure its integrity during service. At the same time, the fine and dense Cr on the surface will preferentially react with oxygen to form a dense layer of Cr2O3, which can significantly inhibit the diffusion of oxygen. The larger equiaxed grains in the middle layer ensure the thermal conductivity of the material and ensure that it can operate under normal conditions. The fine Cr grains in contact with the substrate again act as a barrier to prevent oxygen from diffusing into the zirconium alloy substrate. In addition, the present invention controls the argon flow rate in the sample tube (i.e., controls the tube wall temperature), bias voltage, target-substrate distance, sputtering gas pressure and other parameters, and deposits for different times to obtain a gradient near-equiaxed crystal coating with different thicknesses of each layer. Considering the effect of the Cr coating on the circumferential and axial thermal expansion properties of the zirconium alloy tube, a coating that is too thick will increase the interface stress and cause cracking and other problems, while a coating that is too thin will have insufficient protective effect on the substrate. Therefore, the present invention also limits the thickness of each layer of the gradient near-equiaxed crystal coating.

[0024] The Cr coating improves the toughness and high-temperature oxidation resistance of the zirconium alloy cladding, and can significantly enhance the ability of the fuel cladding to withstand severe reactor accidents. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0026] Figure 1 This is a schematic diagram of the self-modified equipment for high-power pulsed magnetron sputtering;

[0027] Figure 2 BC+IPF diagram of the zirconium alloy sample deposited with Cr coating prepared in Example 1;

[0028] Figure 3 SEM image of the sample prepared in Example 2 after oxidation at 1200°C high temperature steam for 3600s;

[0029] Figure 4 SEM image of the sample prepared in Comparative Example 2 after oxidation under high-temperature steam conditions at 1200°C for 3600s. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] The "room temperature" mentioned in the present invention is 20-30°C unless otherwise specified.

[0036] The present invention adopts high-power pulsed magnetron sputtering (HiPIMS) technology, and by modifying the HiPIMS equipment, argon is introduced into the zirconium alloy cladding tube and the flow rate of argon in the tube is controlled, and the bias voltage, target-substrate distance, sputtering gas pressure and other parameters are combined to adjust and obtain a gradient near-equiaxed Cr coating with grain sizes of 0.1-0.3μm, 1-2μm and 0.1-0.3μm respectively. The gradient coating has small grains close to the zirconium alloy substrate (grain size 0.1-0.3μm), and as the distance from the zirconium alloy increases, the grains gradually become larger (grain size 1-2μm), and the coating surface is composed of a layer of fine and dense fine crystals (grain size 0.1-0.3μm). The overall thickness of the pure Cr coating is 10-15μm, wherein the first coating thickness is 5.0-7.0μm, the second coating thickness is 4.5-6.8μm, and the third coating thickness is 0.5-1.2μm. The pure Cr gradient coating on the surface of the accident-resistant zirconium alloy cladding designed in the present invention exhibits good toughness when oxidized in a high-temperature environment, and a dense Cr2O3 protective oxide film is generated on its surface, which improves the density and uniformity of the material surface and significantly inhibits the diffusion of oxygen, thereby improving its high-temperature oxidation resistance.

[0037] The specific technical solution is: a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding, the gradient coating has near-equiaxed crystal characteristics, is divided into three layers, and has a total thickness of 10-15μm. The coating has smaller grains near the zirconium alloy substrate (the grain size of the first coating is 0.1-0.3μm, and the thickness is 5.0-7.0μm). As the distance from the zirconium alloy increases, the grains gradually become larger (the grain size of the second coating is 1-2μm, and the thickness is 4.5-6.8μm). The surface of the coating is composed of a layer of fine and dense fine crystals (the grain size of the third coating is 0.1-0.3μm, and the thickness is 0.5-1.2μm).

[0038] Pure Cr near-equiaxed crystal coating is a better grain structure with good toughness. When oxidized in a high temperature environment, a dense layer of Cr2O3 is generated on the surface, which is not easy to peel off or crack, ensuring the integrity of the Cr coating on the surface of the zirconium alloy. It can significantly inhibit the diffusion of oxygen, improve the density and uniformity of the material surface, and thus improve its high-temperature oxidation resistance. At the same time, the gradient near-equiaxed crystal structure helps to improve the thermal stability of the material, making it more suitable for high-temperature working environments.

[0039] The present invention also provides a method for preparing the gradient near-equiaxed crystal Cr coating on the surface of the zirconium alloy cladding, which is plated on the base material by a high-power pulsed magnetron sputtering process, comprising the following steps:

[0040] 1) Matrix pretreatment: prepare a Zr-4 alloy tube with the following dimensions: outer diameter 8.5-10.5 mm, thickness 0.45-0.65 mm, length 10-25 cm, composition Zr98.0-98.5%, Sn1.0-2.0%, Fe0.2-0.3%, Cr0.1-0.2%; use 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper to grind the sample surface in turn; then polish with 9μm, 3μm and 1μm diamond suspension; finally, soak the sample in acetone solution and ultrasonically clean it for 10-20 min, take it out, dry it, and put it in a vacuum box for standby use;

[0041] 2) Substrate installation and target pre-sputtering treatment: Fix the pre-treated sample on the sample stage of the magnetron sputtering chamber, heat the magnetron sputtering chamber to 200-350℃, and evacuate the chamber to 3-5×10 -4 Pa, argon gas is introduced into the chamber of the magnetron sputtering instrument until the chamber pressure is 0.8-1.5Pa, and the Cr target is pre-sputtered for 10-25min at a power of 200-500W;

[0042] 3) Argon plasma etching: etching for 10-30 minutes at a temperature of 200-350°C, an argon gas flow rate of 40-60 sccm, an ion source current of 0.5-2A, and a bias voltage of -50 to -200V;

[0043] 4) Sputtering Cr coating: Turn on the high-power pulse sputtering power supply, control the pulse frequency to 200-500Hz, pulse width to 20-80μs, duty cycle to 1-4%, and sputtering power to 2000-4000W. Dynamically control the following parameters: bias voltage -90~-120V, target-substrate distance to 10-20cm, sputtering pressure to 0.2-1.0Pa, control the Ar gas flow rate in the tube to 10-50sccm, deposition temperature to 150-420℃, deposition time for each layer of coating to 0.5-8h, total deposition time to 5-15h, thickness of each layer of coating to 0.5-7μm, and total coating thickness to 10-15μm. To control the grain size and thickness of each layer of near-equiaxed crystal coating, specifically:

[0044] a. Sputtering the first coating: control the bias voltage to -110~-120V, the target-substrate distance to 15-20cm, the sputtering gas pressure to 0.2-0.6Pa, and actively and dynamically adjust the Ar flow rate in the tube to 25-50sccm according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube through the infrared temperature meter-Ar gas flow rate controller system, so that the outer wall temperature of the tube (ie, the deposition temperature) is maintained at 150-260°C, and the deposition is carried out for 2.5-8h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the first coating;

[0045] b. Sputtering the second coating: Control the bias voltage at -90 to -110 V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 10-15 cm, and control the sputtering gas pressure to 0.6-1.0 Pa. Through the infrared temperature meter-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 10-25 sccm, so that the outer wall temperature of the tube (ie, the deposition temperature) is maintained at 260-420 ° C, and the deposition is carried out for 2-6 hours to obtain a larger size near-equiaxed crystal structure, i.e., the second coating;

[0046] c. Sputtering the third coating: control the bias voltage to -110~-120V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 15-20cm, and control the sputtering gas pressure to 0.2-0.6Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 25-50sccm, so that the temperature of the outer wall of the tube (ie, the deposition temperature) is maintained at 150-260℃, and the deposition is carried out for 0.5-1h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the third coating.

[0047] In order to obtain a coating with specified grain morphology, grain size and thickness, the present invention strictly controls the range of parameter values ​​such as bias voltage, target substrate distance, sputtering gas pressure and Ar gas flow rate (deposition temperature) in the tube, so as to obtain the required near-equiaxed crystal characteristic structure with a certain thickness gradient.

[0048] The raw materials used in the following examples of the present invention are all commercially available.

[0049] The following examples serve as further illustrations of the technical solutions of the present invention.

[0050] Embodiment 1:

[0051] A method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding comprises the following steps:

[0052] 1) Matrix pretreatment: prepare a Zr-4 alloy tube with the following dimensions: outer diameter 9.5 mm, thickness 0.57 mm, length 20 cm, composition of Zr98.3%, Sn1.3%, Fe0.25%, Cr0.15%; polish the sample surface with 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper in turn; then polish with 9μm, 3μm and 1μm diamond suspension; finally, soak the sample in acetone solution and ultrasonically clean it for 15 min, take it out, dry it and put it in a vacuum box for standby use;

[0053] 2) Substrate installation and target pre-sputtering treatment: The pre-treated sample was fixed on the sample stage of the magnetron sputtering chamber, the magnetron sputtering chamber was heated to 310°C, and the chamber was vacuumed to 4×10 -4 Pa, argon gas was introduced into the chamber of the magnetron sputtering instrument until the chamber pressure was 1.0 Pa, and the Cr target was pre-sputtered for 15 min at a power of 400 W;

[0054] 3) Argon plasma etching treatment: etching for 25 min at a temperature of 270°C, an argon gas flow rate of 50 sccm, an ion source current of 1.2 A, and a bias voltage of -100 V;

[0055] 4) Sputtering Cr coating: Turn on the high-power pulse sputtering power supply, control the pulse frequency to 360Hz, the pulse width to 80μs, the duty cycle to 3%, and the sputtering power to 2800W. Dynamically control the following parameters: bias voltage -90~-120V, target substrate distance 10-20cm, sputtering gas pressure 0.2-1.0Pa, control the Ar gas flow rate in the tube to 10-50sccm, deposition temperature 150-420℃, deposition time for each layer of coating 0.5-8h, total deposition time 5-15h, thickness of each layer of coating 0.5-7μm, total coating thickness 10-15μm. The specific steps are as follows:

[0056] a. Sputtering the first coating: control the bias voltage to -115V, the target-substrate distance to 16cm, the sputtering gas pressure to 0.4Pa, and actively and dynamically adjust the Ar flow rate in the tube to 25-50sccm according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube through the infrared temperature meter-Ar gas flow rate controller system, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 205-215°C, and the deposition is performed for 4h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the first coating;

[0057] b. Sputtering the second coating: Control the bias voltage to -95V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 13cm, and control the sputtering gas pressure to 0.8Pa. Through the infrared temperature meter-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 10-25sccm, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 305-325°C, and the deposition is carried out for 3.5 hours to obtain a larger size near-equiaxed crystal structure, i.e., the second coating;

[0058] c. Sputtering the third coating: control the bias voltage to -115V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 16cm, and control the sputtering gas pressure to 0.4Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 25-50sccm, so that the temperature of the outer wall of the tube (i.e., the deposition temperature) is maintained at 200-210°C, and the deposition is carried out for 0.5h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the third coating.

[0059] The total deposition time of this embodiment is 8 hours, and a zirconium alloy sample with a Cr coating is obtained. After testing, the total thickness of the coating is 11.0 μm, of which the first coating thickness is 5.3 μm, the second coating thickness is 5.0 μm, and the third coating thickness is 0.7 μm. The average grain size of the first coating is 0.15 μm, the average grain size of the second coating is 1.4 μm, and the average grain size of the third coating is 0.23 μm.

[0060] Figure 2 This is the BC+IPF diagram of the zirconium alloy sample deposited with Cr coating prepared in Example 1. It can be seen from the figure that the coating grains are nearly equiaxed of different sizes and are divided into three layers. The overall thickness of the coating is uniform and the surface is flat. The film-base bonding is strong and the coating is not easy to peel off.

[0061] Embodiment 2:

[0062] A method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding comprises the following steps:

[0063] 1) Matrix pretreatment: prepare a Zr-4 alloy tube with the following dimensions: outer diameter 9.5 mm, thickness 0.57 mm, length 20 cm, composition of Zr98.3%, Sn1.3%, Fe0.25%, Cr0.15%; polish the sample surface with 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper in turn; then polish with 9μm, 3μm and 1μm diamond suspension; finally, soak the sample in acetone solution and ultrasonically clean it for 20 min, take it out, dry it, and put it in a vacuum box for standby use;

[0064] 2) Substrate installation and target pre-sputtering treatment: The pre-treated sample is fixed on the sample stage of the magnetron sputtering chamber, the magnetron sputtering chamber is heated to 280°C, and the chamber is vacuumed to 4×10 -4 Pa, argon gas was introduced into the chamber of the magnetron sputtering instrument until the chamber pressure was 1.2 Pa, and the Cr target was pre-sputtered for 20 min at a power of 350 W;

[0065] 3) Argon plasma etching treatment: etching for 20 min at a temperature of 260°C, an argon gas flow rate of 45 sccm, an ion source current of 1.5 A, and a bias voltage of -110 V;

[0066] 4) Sputtering Cr coating: Turn on the high-power pulse sputtering power supply, control the pulse frequency to 320Hz, the pulse width to 60μs, the duty cycle to 2%, and the sputtering power to 2500W. Dynamically control the following parameters: bias voltage -90~-120V, target substrate distance 10-20cm, sputtering pressure 0.2-1.0Pa, control the Ar gas flow rate in the tube to 10-50sccm, deposition temperature 150-420℃, deposition time for each layer of coating 0.5-8h, total deposition time 5-15h, thickness of each layer of coating 0.5-7μm, total coating thickness 10-15μm. The specific steps are as follows:

[0067] a. Sputtering the first coating: control the bias voltage to -120V, the target-substrate distance to 18cm, the sputtering gas pressure to 0.5Pa, and actively and dynamically adjust the Ar flow rate in the tube to 25-50sccm according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube through the infrared temperature detector-Ar gas flow rate controller system, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 195-205°C, and the deposition is carried out for 6h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the first coating;

[0068] b. Sputtering the second coating: Control the bias voltage to -100V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 14cm, and control the sputtering gas pressure to 0.9Pa. Through the infrared temperature meter-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 10-25sccm, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 300-320°C, and the deposition is carried out for 5 hours to obtain a larger size near-equiaxed crystal structure, i.e., the second coating;

[0069] c. Sputtering the third coating: control the bias voltage to -110V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 17cm, and control the sputtering gas pressure to 0.5Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 25-50sccm, so that the temperature of the outer wall of the tube (i.e., the deposition temperature) is maintained at 205-215°C. Deposition for 1 hour to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the third coating.

[0070] The total deposition time of this embodiment is 12 hours, and a zirconium alloy sample with a Cr coating is obtained. After testing, the total thickness of the coating is 14.4 μm, of which the first coating thickness is 6.5 μm, the second coating thickness is 6.7 μm, and the third coating thickness is 1.2 μm. The average grain size of the first coating is 0.12 μm, the average grain size of the second coating is 1.3 μm, and the average grain size of the third coating is 0.26 μm.

[0071] Embodiment 3:

[0072] A method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding comprises the following steps:

[0073] 1) Matrix pretreatment: prepare a Zr-4 alloy tube with the following dimensions: outer diameter 9.5 mm, thickness 0.57 mm, length 20 cm, composition of Zr98.3%, Sn1.3%, Fe0.25%, Cr0.15%; polish the sample surface with 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper in turn; then polish with 9μm, 3μm and 1μm diamond suspension; finally, soak the sample in acetone solution and ultrasonically clean it for 15 min, take it out, dry it and put it in a vacuum box for standby use;

[0074] 2) Substrate installation and target pre-sputtering treatment: The pre-treated sample is fixed on the sample stage of the magnetron sputtering chamber, the magnetron sputtering chamber is heated to 320°C, and the chamber is vacuumed to 4×10 -4 Pa, argon gas was introduced into the chamber of the magnetron sputtering instrument until the chamber pressure was 1.3 Pa, and the Cr target was pre-sputtered for 25 min at a power of 450 W;

[0075] 3) Argon plasma etching treatment: etching for 20 min at a temperature of 280°C, an argon gas flow rate of 50 sccm, an ion source current of 1.4 A, and a bias voltage of -110 V;

[0076] 4) Sputtering Cr coating: Turn on the high-power pulse sputtering power supply, control the pulse frequency to 400Hz, the pulse width to 50μs, the duty cycle to 3%, and the sputtering power to 3200W. Dynamically control the following parameters: bias voltage -90~-120V, target substrate distance 10-20cm, sputtering gas pressure 0.2-1.0Pa, control the Ar gas flow rate in the tube to 10-50sccm, deposition temperature 150-420℃, deposition time for each layer of coating 0.5-8h, total deposition time 5-15h, thickness of each layer of coating 0.5-7μm, total coating thickness 10-15μm. The specific steps are as follows:

[0077] a. Sputtering the first coating: control the bias voltage to -110V, the target-substrate distance to 15cm, the sputtering gas pressure to 0.3Pa, and actively and dynamically adjust the Ar flow rate in the tube to 25-50sccm according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube through the infrared temperature meter-Ar gas flow rate controller system, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 210-220°C, and the deposition is performed for 4.5h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the first coating;

[0078] b. Sputtering the second coating: Control the bias voltage to -105V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 14cm, and control the sputtering gas pressure to 1.0Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 10-25sccm, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 295-305°C, and the deposition is carried out for 4 hours to obtain a larger size near-equiaxed crystal structure, i.e., the second coating;

[0079] c. Sputtering the third coating: control the bias voltage to -120V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 15cm, and control the sputtering gas pressure to 0.3Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 25-50sccm, so that the temperature of the outer wall of the tube (i.e., the deposition temperature) is maintained at 210-220℃. Deposition for 1 hour to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the third coating.

[0080] The total deposition time of this embodiment is 9.5 hours, and a zirconium alloy sample with a Cr coating is obtained. After testing, the total thickness of the coating is 11.7 μm, of which the first coating thickness is 5.5 μm, the second coating thickness is 5.2 μm, and the third coating thickness is 1.0 μm. The average grain size of the first coating is 0.22 μm, the average grain size of the second coating is 1.2 μm, and the average grain size of the third coating is 0.27 μm.

[0081] Embodiment 4:

[0082] A method for preparing a gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding comprises the following steps:

[0083] 1) Matrix pretreatment: prepare a Zr-4 alloy tube with the following dimensions: outer diameter 9.5 mm, thickness 0.57 mm, length 20 cm, composition of Zr98.3%, Sn1.3%, Fe0.25%, Cr0.15%; polish the sample surface with 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper in turn; then polish with 9μm, 3μm and 1μm diamond suspension; finally, soak the sample in acetone solution and ultrasonically clean it for 15 min, take it out, dry it and put it in a vacuum box for standby use;

[0084] 2) Substrate installation and target pre-sputtering treatment: The pre-treated sample is fixed on the sample stage of the magnetron sputtering chamber, the magnetron sputtering chamber is heated to 300°C, and the chamber is vacuumed to 4×10 -4 Pa, argon gas was introduced into the chamber of the magnetron sputtering instrument until the chamber pressure was 0.8 Pa, and the Cr target was pre-sputtered for 15 min at a power of 400 W;

[0085] 3) Argon plasma etching treatment: etching for 20 min at a temperature of 280°C, an argon gas flow rate of 50 sccm, an ion source current of 1.2 A, and a bias voltage of -110 V;

[0086] 4) Sputtering Cr coating: Turn on the high-power pulse sputtering power supply, control the pulse frequency to 350Hz, the pulse width to 50μs, the duty cycle to 3%, and the sputtering power to 2500W. Dynamically control the following parameters: bias voltage -90~-120V, target substrate distance 10-20cm, sputtering pressure 0.2-1.0Pa, control the Ar gas flow rate in the tube to 10-50sccm, deposition temperature 150-420℃, deposition time for each layer of coating 0.5-8h, total deposition time 5-15h, thickness of each layer of coating 0.5-7μm, total coating thickness 10-15μm. The specific steps are as follows:

[0087] a. Sputtering the first coating: control the bias voltage to -110V, the target-substrate distance to 16cm, the sputtering gas pressure to 0.2Pa, and actively and dynamically adjust the Ar flow rate in the tube to 25-50sccm according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube through the infrared temperature meter-Ar gas flow rate controller system, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 225-235°C, and the deposition is carried out for 3.5h to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the first coating;

[0088] b. Sputtering the second coating: Control the bias voltage to -90V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 12cm, and control the sputtering gas pressure to 0.7Pa. Through the infrared temperature meter-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 10-25sccm, so that the outer wall temperature of the tube (i.e., the deposition temperature) is maintained at 320-340°C, and the deposition is carried out for 3 hours to obtain a larger size near-equiaxed crystal structure, i.e., the second coating;

[0089] c. Sputtering the third coating: control the bias voltage to -120V, control the connecting rod through the servo motor, slowly move the Cr target within 1 minute so that the target-substrate distance becomes 18cm, and control the sputtering gas pressure to 0.5Pa. Through the infrared temperature sensor-Ar gas flow rate controller system, according to the real-time temperature monitoring data of the outer wall of the Zr-4 alloy tube, actively and dynamically adjust the Ar flow rate in the tube at 25-50sccm, so that the temperature of the outer wall of the tube (i.e., the deposition temperature) is maintained at 190-200°C. Deposition is performed for 1 hour to obtain a fine, dense, nearly equiaxed crystal structure, i.e., the third coating.

[0090] The total deposition time of this embodiment is 7.5h, and a zirconium alloy sample with a Cr coating is obtained. After testing, the total thickness of the coating is 10.8μm, of which the first coating thickness is 5.2μm, the second coating thickness is 4.8μm, and the third coating thickness is 0.8μm. The average grain size of the first coating is 0.25μm, the average grain size of the second coating is 1.6μm, and the average grain size of the third coating is 0.18μm.

[0091] Comparative Example 1:

[0092] Same as Example 1, except that the bias voltages of the sputtering first, second and third coatings in step 4) are -95V, -75V and -90V respectively, and the other parameters are consistent with Example 1. The grain morphology of the obtained coating tends to be a columnar crystal structure, and there is cracking, which does not meet the requirements. The columnar crystal structure of the coating is not conducive to the toughness of the coating and is prone to cracking or falling off of the coating. And the second coating of the coating sample loses the nearly equiaxed crystal characteristics, which is not conducive to improving the high temperature oxidation resistance of the sample.

[0093] Comparative Example 2:

[0094] The same as Example 2, except that in step 4), the target-substrate distances for sputtering the first, second and third coatings are 12 cm, 8 cm and 12 cm respectively, and the other parameters are consistent with Example 2. The obtained coatings have coarse grains, and the average grain sizes are 1.27 μm, 4.5 μm and 1.78 μm respectively, which do not meet the requirements.

[0095] Coarse grains reduce the toughness and strength of the material because larger grains reduce the number of grain boundaries, which can prevent crack propagation. This will cause the coating to crack or fall off more easily when subjected to external forces. In addition, the density of grain boundaries of coarse grains decreases, which is not conducive to the rapid formation of protective Cr2O3 oxide film on the surface in an oxidizing or corrosive environment, and the protective effect on the substrate decreases.

[0096] Comparative Example 3:

[0097] The same as Example 3, except that in step 4), the sputtering gas pressures of the first, second and third coatings are 0.8Pa, 1.2Pa and 0.8Pa respectively, and the other parameters are consistent with Example 3. The resulting coating has poor crystallization effect and poor organizational state and cannot meet the requirements.

[0098] Comparative Example 4:

[0099] The same as Example 4, except that in step 4), the Ar gas flow rates in the tube for sputtering the first, second and third coatings are 10-25sccm, 5-15sccm and 10-25sccm respectively, the deposition temperatures are controlled to be 250-280°C, 365-395°C and 250-280°C respectively, and the other parameters are consistent with Example 4. The average grain sizes of the obtained first, second and third coatings are 0.86μm, 4.7μm and 0.75μm respectively, the grains are coarse, the grain boundary density is reduced, the toughness is reduced, the protection of the coating to the substrate is reduced, and the comparative example also loses the fine and dense nearly equiaxed crystal structure characteristics of the first and third coatings, which does not meet the requirements.

[0100] Performance Testing:

[0101] The zirconium alloy samples deposited with Cr coating prepared in the above Example 2 and Comparative Example 2 were subjected to high-temperature steam oxidation tests, and the method was as follows: The high-temperature steam oxidation test was carried out in a horizontal tube furnace equipped with a steam generator, and the temperature was raised from room temperature to a specified temperature of 1200°C at a heating rate of 10°C / min, and flowing Ar gas (purity of 99.999%) was introduced during the heating process to protect the sample from initial oxidation. When the expected temperature was reached, flowing steam was introduced into the tube at a rate of 2g / min, and once the steam flow was stable, the sample was placed in the center of the furnace. All samples were kept at 1200°C for 3600s and then air-cooled to room temperature.

[0102] The results are as follows: the zirconium alloy sample with Cr coating in Example 2 has excellent resistance to high-temperature steam oxidation, the thickness of Cr2O3 is thinner and more uniform, there is no peeling of oxide film and residual Cr coating after oxidation, and there is no debonding at the coating-substrate interface.

[0103] Figure 3This is a SEM picture of the sample prepared in Example 2 after oxidation at 1200°C high temperature steam for 3600s. It can be seen from the figure that the thickness of Cr2O3 after oxidation is 7.74μm, the thickness of residual Cr is 8.36μm, the coating thickness is dense and uniform, there is no crack, hole, or peeling phenomenon, and the coating has good protection for the zirconium alloy substrate.

[0104] Figure 4 This is a SEM image of the sample prepared in Comparative Example 2 after oxidation for 3600s under high-temperature steam conditions at 1200°C. It can be seen from the figure that the pure Cr coating has poor toughness, severe cracking and peeling, and the Cr coating is completely oxidized to Cr2O3, with no residual Cr coating. The discontinuous oxide layer in this comparative example does not have a protective function and cannot effectively protect the Zr alloy substrate.

[0105] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A gradient near-equiaxed Cr coating on the surface of a zirconium alloy cladding, characterized in that: The coating has a near-equiaxed crystal feature and is divided into three layers with a total thickness of 10-15 μm, wherein the grain size of the first coating is 0.1-0.3 μm and the thickness is 5.0-7.0 μm; the grain size of the second coating is 1-2 μm and the thickness is 4.5-6.8 μm; the grain size of the third coating is 0.1-0.3 μm and the thickness is 0.5-1.2 μm; The method for preparing the gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding comprises the following steps: The pretreated zirconium alloy substrate is subjected to target pre-sputtering treatment and argon plasma etching treatment, and then a Cr coating is sputtered to obtain the gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding; Among them, in the process of sputtering Cr coating, three-layer coatings with different grain sizes are obtained by the following strategies: A. Regulating the bias voltage: When preparing the first coating or the third coating, the bias voltage is regulated to -110 to -120 V; when preparing the second coating, the bias voltage is regulated to -90 to -110 V; B. Adjust the target-substrate distance: when preparing the first coating or the third coating, the target-substrate distance is 15-20cm; when preparing the second coating, the target-substrate distance is 10-15cm; C. Regulating the sputtering pressure: When preparing the first coating or the third coating, the sputtering pressure is 0.2-0.6Pa; when preparing the second coating, the sputtering pressure is 0.6-1.0Pa; D. Regulating the argon flow rate and tube wall temperature in the tube: When preparing the first coating or the third coating, the argon flow rate in the tube is controlled to 25-50 sccm to adjust the tube wall temperature to 150-260°C; when preparing the second coating, the argon flow rate in the tube is controlled to 10-25 sccm to adjust the tube wall temperature to 260-420°C.

2. The gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding according to claim 1 is characterized in that: When sputtering the first coating, the deposition time is 2.5-8 hours; when sputtering the second coating, the deposition time is 2-6 hours; when sputtering the third coating, the deposition time is 0.5-1 hour.

3. The gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding according to claim 1 is characterized in that: The pretreatment method is: using 400#, 800#, 1200#, 2000#, 3000# and 4000# sandpaper to grind the surface of the zirconium alloy substrate in sequence, and then polishing with 9μm, 3μm and 1μm diamond suspension in sequence; finally, immersing the sample in an acetone solution for ultrasonic cleaning for 10-20 minutes, taking it out, drying it, and putting it in a vacuum box for standby use.

4. The gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding according to claim 1 is characterized in that: During the target pre-sputtering process, the temperature of the magnetron sputtering chamber is 200-350°C, and the vacuum of the chamber is 3-5×10 -4 Pa, high-purity argon gas is introduced to make the chamber pressure 0.8-1.5Pa, the power is 200-500W, and the sputtering time is 10-25min.

5. The gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding according to claim 1 is characterized in that: During the argon plasma etching process, the temperature is 200-350° C., the argon gas flow rate is 40-60 sccm, the ion source current is 0.5-2A, the bias voltage is -50 to -200V, and the etching time is 10-30min.

6. The gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding according to claim 1, characterized in that: In the sputtering process of the Cr coating, the pulse frequency is 200-500 Hz, the pulse width is 20-80 μs, the duty cycle is 1-4%, the sputtering power is 2000-4000 W, the deposition temperature is 150-420° C., and the deposition time is 5-15 hours.

7. Use of the gradient near-equiaxed Cr coating on the surface of the zirconium alloy cladding as claimed in claim 1 in improving the high temperature service performance of the zirconium alloy cladding tube.